2003
DOI: 10.1088/0031-9155/48/22/001
|View full text |Cite
|
Sign up to set email alerts
|

A functionalized THz sensor for marker-free DNA analysis

Abstract: We report on a novel resonant THz sensor for the label-free analysis of DNA molecules. The sensor allows the direct detection of DNA-probe molecules at functionalized electrodes via hybridization. Subsequent time resolved photoconductive sampling of the THz transmission identifies the binding state between probe and target DNA. Integrating neighbouring sensors on a chip, this technique can be extended to a parallel analysis of multiple DNA sequences. A clearly readable sensor response is obtained with less the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 27 publications
1
95
0
1
Order By: Relevance
“…Future prospects of THz technology are discussed. Nagel et al [Nagel et al, 2003] first reported a novel resonant THz sensor for the label-free analysis of DNA molecules. The sensor allows the direct detection of DNA-probe molecules at functionalized electrodes via hybridization.…”
Section: Sensorsmentioning
confidence: 99%
“…Future prospects of THz technology are discussed. Nagel et al [Nagel et al, 2003] first reported a novel resonant THz sensor for the label-free analysis of DNA molecules. The sensor allows the direct detection of DNA-probe molecules at functionalized electrodes via hybridization.…”
Section: Sensorsmentioning
confidence: 99%
“…THz waves are unique, having properties of both electrical and optical waves. Various applications of THz waves have been reported in many fields, including medical diagnosis, pharmaceutical analysis and security enhancement (Nagel et al, 2003;Woodward et al, 2003;Yamamoto et al, 2004aYamamoto et al, , 2004bKawase et al, 2003;Hineno et al, 1974;Taday et al, 2003;Walther et al, 2002). Absorption spectra in the THz range provide rich information for both intermolecular and intramoleculer interactions, including inter-ring interactions of disaccharides (Hineno et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] THz time-domain spectroscopy (THz-TDS) is useful for measuring the optical properties between 3 cm -1 (0.1 THz) and 100 cm -1 (3 THz), and gives a better signal-to-noise ratio than far-infrared Fourier transform (FIR FT-IR) spectroscopy. 9,10 Absorption spectra in the THz range are very sensitive to differences in the crystal structure, 11 and are applied to study the polymorphs of medicines.…”
Section: Introductionmentioning
confidence: 99%